FREQUENCY OF ACTINOBACILLUS PLEUROPNEUMONIAE INFECTION IN COMMERCIAL PIG FARMS OF THE PERUVIAN COAST - Pinto J., Chris (2010)
The objective of the study was to determine the frequency of antibodies against the ApxIV toxin of Actinobacillus pleuropneumoniae, causal agent of porcine pleuropneumonia in 10 commercial pig farms of Arequipa, Lima, Ica and La Libertad departments. Blood samples were collected from animals in the growing and finishing stages (30 per farm) and analyzed by the indirect ELISA test using a commercial kit. The results showed that 23.7% (71/300) of the animals presented antibodies against the ApxIV toxin, and the highest frequency was found in the farm located in Ica (60%). The presence of antibodies against the ApxIV toxin indicated the presence of A. pleuropneumoniae infection in pig commercial farms in Peru.